GAS FIELDS AND RESERVES (Academicia Globe: Inderscience Research, 2023)
Information is provided on gas fields, leading countries in gas production, gas reserves, gas fields in Uzbekistan, gas reserves, volume and share of gas production in Uzbekistan.